The role of human resource managers in the promotion of hotel sector as a brand in Jordanian hotel industry: A cross-sectional study - Naser Khdour (Cogent Business & Management, 2021)
This study assesses the impact of human resource managers on the effectiveness of hotel branding with reference to Jordanian hotel industry. The study followed a cross-sectional design in which data was collected through a questionnaire-based survey. Subsequently, the collected data were analysed using descriptive and multiple regression analysis. Findings of the study revealed that job satisfaction of the employee, employee effectiveness, employee selection, and employee retention strongly and significantly impact the brand promotion and are the focus of interest of HR managers. The results concluded that effective HR policies and practices can ensure improved performance of the hotel sector.
Keywords: 650; Human resource practices; brand performance; hospitality industry; hotels; jordan